Ion Channels as Potential Tools for the Diagnosis, Prognosis, and Treatment of HPV-Associated Cancers - Andrea Jazmín Chiliquinga; Brenda Acosta; Ingrid Ogonaga-Borja; Fernanda Villarruel-Melquiades; Jaime de la Garza; Patricio Gariglio; Rodolfo Ocádiz-Delgado; Ana Ramírez; Yesennia Sánchez-Pérez; Claudia M. García-Cuellar; Cecilia Bañuelos; Javier Camacho (Cells, 2023)
The human papilloma virus (HPV) group comprises approximately 200 genetic types that have a special affinity for epithelial tissues and can vary from producing benign symptoms to developing into complicated pathologies, such as cancer. The HPV replicative cycle affects various cellular and molecular processes, including DNA insertions and methylation and relevant pathways related to pRb and p53, as well as ion channel expression or function. Ion channels are responsible for the flow of ions across cell membranes and play very important roles in human physiology, including the regulation of ion homeostasis, electrical excitability, and cell signaling. However, when ion channel function or expression is altered, the channels can trigger a wide range of channelopathies, including cancer. In consequence, the up- or down-regulation of ion channels in cancer makes them attractive molecular markers for the diagnosis, prognosis, and treatment of the disease. Interestingly, the activity or expression of several ion channels is dysregulated in HPV-associated cancers. Here, we review the status of ion channels and their regulation in HPV-associated cancers and discuss the potential molecular mechanisms involved. Understanding the dynamics of ion channels in these cancers should help to improve early diagnosis, prognosis, and treatment in the benefit of HPV-associated cancer patients.